2007
DOI: 10.1002/jssc.200700130
|View full text |Cite
|
Sign up to set email alerts
|

Retention effects of oxidized polyphenols during analytical extraction of phenolic compounds of virgin olive oil

Abstract: The hydrophilic extract of virgin olive oil contains several phenolic compounds such as simple phenols, lignans, and secoiridoids that have been widely studied in recent years. Interest in the hydrophilic extract has also been extended to the fraction of oxidized phenols that form during storage as a consequence of oxidative stress. The present investigation compares the two most commonly used extraction methods, namely liquid-liquid extraction and SPE, on fresh virgin olive oil and that kept at different temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
1
14
0
2
Order By: Relevance
“…5. Partial identification was achieved by comparing their retention times with those of the oxidised phenols previously found after conventional oven treatment at 180°C (Carrasco-Pancorbo , 2007), as well as after storage at 50°C for several months (Armaforte et al, 2007). However, due to their low presence level, it was not possible to obtain neat mass spectra that confirmed their identification.…”
Section: Phenolic Compoundsmentioning
confidence: 98%
See 1 more Smart Citation
“…5. Partial identification was achieved by comparing their retention times with those of the oxidised phenols previously found after conventional oven treatment at 180°C (Carrasco-Pancorbo , 2007), as well as after storage at 50°C for several months (Armaforte et al, 2007). However, due to their low presence level, it was not possible to obtain neat mass spectra that confirmed their identification.…”
Section: Phenolic Compoundsmentioning
confidence: 98%
“…This is probably due to its high thermo-lability, as previously observed in oven heating at 180°C (Carrasco-Pancorbo et al, 2007). Armaforte et al, 2007). For peak identification see Fig.…”
Section: Phenolic Compoundsmentioning
confidence: 98%
“…Five oxidation phenols were identified with gas-chromatography. Armaforte et al [125] showed that SPE procedure (usually used to extract the phenolic fraction from VOO) may be a not appropriate analytical step when VOO contains significant polar oxidation products (from phenols or lipids); in fact, these latter compounds could interfere with the retention mechanism of phenols during their extraction. These authors also proposed an index to establish the degree of freshness of VOO.…”
Section: Phenols As Related To Oxidative Stability Of Voomentioning
confidence: 99%
“…Rovellini, Cortesi, and Fedeli (1998) have proposed a method to evaluate the oxidation status of VOOs using RP-HPLC analysis of OFAs. This method has been used in various areas of applied research for VOO (Armaforte et al, 2007;Bendini et al, 2006;Rovellini & Cortesi, 2004) as well as for the analysis of lipid extracts from other matrices (Verardo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%